A Note on Intensionalization - de Groote, Philippe; Kanazawa, Makoto (Journal of logic, language, and information, 2013)
Building on Ben-Avi and Winter's (2007) work, this paper provides a general "intensionalization" procedure that turns an extensional semantics for a language into an intensionalized one that is capable of accommodating "truly intensional" lexical items without changing the compositional semantic rules. We prove some formal properties of this procedure and clarify its relation to the procedure implicit in Montague's (1973) PTQ.